The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/eap.2482
|View full text |Cite
|
Sign up to set email alerts
|

Assessing carnivore spatial co‐occurrence and temporal overlap in the face of human interference in a semiarid forest

Abstract: Apex predators drive top-down effects in ecosystems and the loss of such species can trigger mesopredator release. This ecological process has been well documented in humanmodified small areas, but for management and conservation of ecological communities, it is important to know which human factors affect apex predator occurrence and which mediate mesopredators release at large scales. We hypothesized that mesopredators would avoid spatial and temporal overlap with the apex predator, the puma; but that human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Although previous research has revealed that several species can modify their temporal activity patterns according to factors such as predation risk or human disturbance 22,39 , the circadian rhythms of genets and martens were predominately nocturnal and consistent among predation risk scenarios and seasons 23,40 . However, these mesocarnivores showed temporal segregation with the Iberian lynx, in contrast to Sarmento et al 33 findings for a more diurnal and adaptable mesopredator, the red fox.…”
Section: Discussionmentioning
confidence: 91%
“…Although previous research has revealed that several species can modify their temporal activity patterns according to factors such as predation risk or human disturbance 22,39 , the circadian rhythms of genets and martens were predominately nocturnal and consistent among predation risk scenarios and seasons 23,40 . However, these mesocarnivores showed temporal segregation with the Iberian lynx, in contrast to Sarmento et al 33 findings for a more diurnal and adaptable mesopredator, the red fox.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of predators, or greater use of preferred sites, could reduce the likelihood of prey occurrence, or alter prey co-occurrence patterns according to species-specific responses to increased predation risk [28,30]. In the calde ´n woodland region, tinamou species share similar predators [50]. We found that the distribution of each tinamou species could be related to the presence of one or two predator species.…”
Section: Plos Onementioning
confidence: 80%
“…We installed 16 single, remote cameras (Digital Moultrie Game Spy 4.0 Camera, EBSCO Industries) at regular intervals (2-3 km) in a 4×4 array within each selected 10×10 km square (Fig 1 ) between September 2010 and March 2013, for a total of 720 sites. Although the distance between cameras was relatively long for our study organisms, this sampling design allowed us to record large carnivores and better estimate the occurrence of potential tinamou predators [50]. We installed and georeferenced the cameras along dirt roads, wildlife and cattle trails, following standard practices [20,24,51], operating four grids simultaneously.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, these shifts allow species to utilize the same spaces and resources they would have otherwise abandoned, allowing for greater coexistence (Carter & Linnell, 2016), though responses likely vary by species and community assemblage. High human densities can alter predator community structures through mesopredator and prey release from top‐down pressures (Shamoon et al., 2018; Wang et al., 2019; Zanón Martínez et al., 2022). In some instances, human activity may create spatial refuges for prey (Muhly et al., 2011), and prey may deliberately select locations with high human densities to shield themselves from apex predators (Gordon et al., 2015).…”
Section: Introductionmentioning
confidence: 99%